Sustained-release material for improving fracture resistance of cement-based material and application
By using alkali-excited sustained release capsules in cement-based materials to initiate polymerization, the problems of reducing compressive strength and difficult to control the polymerization process in the prior art are solved, and the effect of efficiently improving flexural properties and maintaining compressive strength is achieved.
Patent Information
- Application Number
- CN202310987717.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-07
AI Technical Summary
When the prior art improves the toughness of concrete, it often leads to a reduction in compressive strength and cannot effectively control the matching between the polymerization process and the hydration process, resulting in uncontrollable performance.
Alkaline-excited sustained release capsules are used as carriers to introduce active initiation components, so that they are broken during the hydration of cement-based materials, initiate polymerization in situ, control polymerization time, and avoid excessive polymer particles and affecting mechanical properties.
It effectively improves the flexural resistance of cement-based materials, while maintaining or optimizing compressive strength, achieving adjustability of performance, and the process is simple and easy to control, safe and environmentally friendly.
Smart Images

Figure CN119430734A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building material admixtures, and in particular, relates to a slow-release material for improving the flexural resistance of cement-based materials and its application. Background Art
[0002] At present, concrete toughening includes fiber toughening, polymer toughening and nanomaterial toughening, which adjust the microstructure of concrete at various scales to improve the tensile strength and fracture energy of concrete. However, these toughening methods all have shortcomings: steel fiber toughening is the most widely used among fiber toughening and has an industrial application basis, but steel fibers are easy to agglomerate and do not improve the toughness of the concrete matrix; in direct addition of polymer toughening, the polymer itself affects cement hydration and is easy to form defects in concrete; in nanomaterial toughening, nanomaterials are easy to agglomerate and are difficult to apply industrially.
[0003] Common and easy-to-operate cement-polymer paste mixing methods include directly mixing cement with polymers as binders or additives, or immersing hardened cement paste in polymer solutions. This single physical addition and blending method has many disadvantages, which makes it impossible to effectively optimize the performance of modified concrete. Most experimental results show that the flexural strength of the material is significantly improved, but the compressive strength is reduced after the addition and modification of the polymer. Therefore, when adding polymer solution, a high dosage will lead to slow setting, low hydration degree, and insignificant flexural strength enhancement effect; when adding polymer emulsion, the size of the organic polymer phase ranges from 10 to 500 μm, forming "macro defects" in the cement matrix, and the larger the size of the polymer phase, the more obvious its mechanical strength weakening effect. Therefore, the current polymer addition method toughens concrete while sacrificing the compressive strength of concrete. These shortcomings have greatly limited its widespread application in modern concrete. Achieving the improvement of concrete toughness is currently a research hotspot and difficulty at home and abroad.
[0004] In order to solve this problem, in-situ polymerization is a method that researchers currently agree is more feasible. Small molecule monomers are added to concrete without polymerization, and polymer polymerization is initiated while cement is hydrated, thus achieving in-situ polymerization in cement-based materials. However, current in-situ polymerization processes are unable to control the polymerization process, and the polymerization process is difficult to match with the hydration process, making it impossible to prepare polymer / cement-based composite materials with adjustable and controllable performance. Controlling the polymer polymerization time so that the monomers do not polymerize before cement hydration and do not affect cement hydration, while avoiding the polymer particles from being too large, causing phase separation in the cement matrix and affecting the mechanical properties of cement-based materials, is a difficulty that needs to be overcome in current research. Summary of the invention
[0005] In order to solve the technical problem of enhancing the toughness of concrete without affecting the compressive strength of concrete in the prior art, the present invention provides a sustained-release material for improving the flexural resistance of cement-based materials. The sustained-release capsules contained in the sustained-release material use alkali-activated capsule sustained-release materials as carriers, and active initiating components are introduced into the sustained-release material so that they can be broken during the hydration process of the cement-based material, thereby initiating polymerization in situ in the cement-based material, achieving the purpose of controlling the polymerization time, so that the monomers do not polymerize before the cement is hydrated, and do not affect the cement hydration. At the same time, it is avoided that the polymer particles are too large, the phase separation is formed in the cement matrix, and the mechanical properties of the cement-based material are affected, and the toughness of the cement-based material can be effectively increased.
[0006] On the other hand, the present invention also provides an application of a slow-release material for improving the flexural resistance of cement-based materials.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A sustained-release material for improving the flexural resistance of cement-based materials, comprising a solution A and a solution B; the solution A is a mixture of alkali-activated sustained-release capsules and a monomer solution; the monomer solution is an acrylamide solution or a sodium acrylate solution, and the solution B is an oxidative initiator solution;
[0009] The alkali-stimulated sustained-release capsule comprises an inner core, an intermediate coating layer and an outer coating layer; the inner core is nano-silicon dioxide, the intermediate coating layer is nano-silicon dioxide modified with tertiary amine groups, and the outer coating layer is nano-silicon dioxide;
[0010] The mass ratio of the effective ingredient in the monomer solution to the alkali-stimulated sustained-release capsule is 30:1-30;
[0011] The mass ratio of the effective components in the monomer solution to the effective components in solution B is 30:0.03-0.3.
[0012] Furthermore, the inner core has a diameter of 70-120 nm, the middle coating layer has a thickness of 6-14 nm, and the outer coating layer has a thickness of 8-20 nm.
[0013] The nano silicon dioxide modified with tertiary amine groups is prepared by siloxane hydrolysis of diethylaminomethyltriethoxysilane (ND-22).
[0014] Furthermore, the oxidative initiator may be selected from sodium persulfate and ammonium persulfate.
[0015] In another aspect, the present invention also provides a method for preparing the alkali-stimulated sustained-release capsule, which specifically comprises the following steps:
[0016] (1) adding an alkaline solution to an organic solvent to adjust the pH value of the solution system to 11-13; then adding tetraethyl orthosilicate thereto to obtain a precursor solution; mechanically stirring the precursor solution to obtain a suspension;
[0017] (2) adding an alcohol solution of tetraethyl orthosilicate to the suspension to cause a siloxane hydrolysis reaction; after the reaction is completed, a core nano-silica is obtained;
[0018] (3) continuing to raise the temperature of the reaction system to 50-60° C., while adding diethylaminomethyltriethoxysilane to cause a siloxane hydrolysis reaction, and after the reaction is completed, coating the intermediate coating layer onto the surface of the inner core nano-silica;
[0019] (4) The reaction system is cooled to room temperature, and an alcohol solution of tetraethyl orthosilicate is continuously added to the reaction system to cause a siloxane hydrolysis reaction. After the reaction is completed, the reaction product is post-treated to obtain a solid sample, which is an alkali-activated sustained-release capsule.
[0020] Furthermore, the alkaline solution in step (1) is one or a combination of sodium hydroxide solution and ammonia water; and the organic solvent in step (1) is ethanol or isopropanol.
[0021] Furthermore, the mechanical stirring speed in step (1) is 300-500 rpm, and the stirring time is 2-3 hours.
[0022] The mass proportions of the raw materials used in the preparation method of the alkali-activated sustained-release capsules are as follows: 2-5 parts of tetraethyl orthosilicate in the step (1), 1-3 parts of tetraethyl orthosilicate in the step (2), 1-3 parts of diethylaminomethyltriethoxysilane in the step (3), and 2-5 parts of tetraethyl orthosilicate in the step (4).
[0023] The present invention also provides an application of a slow-release material for improving the flexural resistance of cement-based materials, wherein solution A and solution B in the slow-release material for improving the flexural resistance of cement-based materials are added to cement-based materials respectively, wherein the mass of the effective component of the monomer solution is 1%-3% of the total mass of the gelling material in the cement-based material.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The method for increasing the flexural resistance provided by the present invention, wherein the effective component is nano-silicon dioxide. Since nano-silicon dioxide itself is a very good reinforcing material, its special volcanic ash activity can react with cement-based materials, optimize the structure and composition of hydration products, and strengthen cement-based materials.
[0026] 2. The method for strengthening cement-based materials provided by the present invention uses a small molecular monomer, diethylaminomethyltriethoxysilane, rather than a polymer, which has little effect on cement-based materials and does not affect the hydration of cement-based materials while improving the flexural properties.
[0027] 3. The active ingredient, nano-silica, has a sustained release effect. It does not expose active amino functional groups during early hydration. After a period of hydration, that is, after the silica shell has dissolved for a period of time, the active amino components are exposed to initiate polymerization, thereby minimizing the effect of the polymer on cement hydration.
[0028] 4. The preparation method provided by the present invention has a wide range of raw material sources, is safe and environmentally friendly, and the preparation process is simple and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a schematic diagram of the structure of the alkali-stimulated sustained-release capsule prepared in Example 8 of the present invention;
[0030] Figure 2 is a SEM image of the alkali-stimulated sustained-release capsule prepared in Example 8 of the present invention;
[0031] Figure 3 is the change in size during the preparation of alkali-stimulated sustained-release capsules in Example 8 of the present invention;
[0032] Figure 4 This is the release curve of the alkali-stimulated sustained-release capsule prepared according to Example 8 of the present invention in solution. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0036] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11.5 with sodium hydroxide, and then 2 mL of tetraethyl orthosilicate was added to the solution.
[0037] The solution obtained above was mechanically stirred at 300 rpm for 2 hours.
[0038] 1 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silicon dioxide with a core diameter of about 70 nm.
[0039] The temperature was raised to 60°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 6 nm.
[0040] The mixture was cooled to room temperature, and 5 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 20 nm.
[0041] The solution obtained above was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S1.
[0042] Example 2
[0043] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0044] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 12 with aqueous ammonia, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0045] The solution obtained above was mechanically stirred at 300 rpm for 2 hours.
[0046] 3 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 120 nm.
[0047] The temperature was raised to 60°C, 3 mL of ND-22 was added to the solution, and the solution was stirred for 2 hours. The thickness of the intermediate coating layer was about 14 nm.
[0048] The temperature was lowered to room temperature, and 2 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 8 nm.
[0049] The solution obtained above was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S2.
[0050] Example 3
[0051] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0052] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11 with aqueous ammonia, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0053] The solution obtained above was mechanically stirred at 300 rpm for 2 hours.
[0054] 3 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 120 nm.
[0055] The temperature was raised to 60°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 6 nm.
[0056] The mixture was cooled to room temperature, and 3 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 15 nm.
[0057] The obtained solution was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S3.
[0058] Example 4
[0059] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0060] 60 g of isopropanol was added to the container, the pH value of the system was adjusted to 12.5 with aqueous ammonia, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0061] The solution obtained above was mechanically stirred at 300 rpm for 2 hours.
[0062] 3 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 120 nm.
[0063] The temperature was raised to 55°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 6 nm.
[0064] The mixture was cooled to room temperature, and 5 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 20 nm.
[0065] The obtained solution was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S4.
[0066] Example 5
[0067] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0068] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11.5 with sodium hydroxide, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0069] The solution obtained above was mechanically stirred at 300 rpm for 3 hours.
[0070] 3 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 120 nm.
[0071] The temperature was raised to 60°C, 2 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 10 nm.
[0072] The mixture was cooled to room temperature, and 5 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 20 nm.
[0073] The obtained solution was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S5.
[0074] Example 6
[0075] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0076] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11.5 with sodium hydroxide, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0077] The solution obtained above was mechanically stirred at 300 rpm for 3 hours.
[0078] 1 mL of tetraethyl silicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 100 nm.
[0079] The temperature was raised to 60°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 6 nm.
[0080] The mixture was cooled to room temperature, and 5 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 20 nm.
[0081] The solution obtained above was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S6.
[0082] Example 7
[0083] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0084] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11.5 with sodium hydroxide, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0085] The solution obtained above was mechanically stirred at 300 rpm for 3 hours.
[0086] 3 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 120 nm.
[0087] The temperature was raised to 50°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 6 nm.
[0088] The mixture was cooled to room temperature, and 5 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 20 nm.
[0089] The solution obtained above was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S7.
[0090] Example 8
[0091] The alkali-stimulated sustained-release capsules provided in this embodiment are prepared by the following method:
[0092] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11 with sodium hydroxide, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0093] The solution obtained above was mechanically stirred at 300 rpm for 3 hours.
[0094] 3 mL of tetraethyl silicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silicon dioxide with a core diameter of about 120 nm.
[0095] The temperature was raised to 50°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The thickness of the intermediate coating layer was about 6 nm.
[0096] The temperature was lowered to room temperature, and 2 mL of an alcohol solution of tetraethyl orthosilicate dispersed in 20 g of ethanol was continuously added dropwise to the suspension. The mixture was reacted for 2 h, and the thickness of the outer coating layer was about 8 nm.
[0097] The solution obtained above was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and vacuum dried to obtain sample S8.
[0098] Comparative Example 1
[0099] This comparative example is set up based on Example 3, the difference being that the outer coating layer is not coated with nano-silica.
[0100] The alkali-stimulated sustained-release capsules provided in this comparative example are prepared by the following method:
[0101] 60 g of ethanol was added to the container, the pH value of the system was adjusted to 11 with aqueous ammonia, and then 5 mL of tetraethyl orthosilicate was added to the solution.
[0102] The solution obtained above was mechanically stirred at 300 rpm for 2 hours.
[0103] 3 mL of tetraethyl orthosilicate solution dispersed in 20 g of ethanol was added dropwise to the solution obtained above at a dropping speed of 1 mL / min to obtain nano-silica with a core diameter of about 120 nm.
[0104] The temperature was raised to 60°C, 1 mL of ND-22 was added to the solution, and the mixture was stirred for 2 hours. The coating thickness was about 6 nm. The mixture was cooled to room temperature, and the solution was centrifuged at 8000 rpm to obtain a solid sample, which was washed twice with ethanol solution and dried in vacuo to obtain sample SD1.
[0105] Application Examples
[0106] Figure 1 This is a schematic diagram of the structure of the alkali-activated sustained-release capsule prepared in Example 8; Figure 2 This is an electron microscope scanning image of the alkali-stimulated sustained-release capsule prepared in Example 8.
[0107] The particle size change of the alkali-activated sustained-release capsules prepared in Example 8 during the synthesis process was tested by dynamic light scattering (DLS). The test results are as follows: Figure 3 As shown. The initial core radius is 58.98nm and the diameter is 117.96nm. After adding ND-22, the radius is 65.27nm. After adding tetraethyl orthosilicate, the radius is 73.38nm. Through the particle size change test, it can be analyzed that the nano-silica is gradually increasing, which means that each layer of coating is effective.
[0108] The release rate of nano-silicon dioxide in water and alkaline solution was tested for the alkali-activated sustained-release capsule prepared in Example 8. The mass of the alkali-activated sustained-release capsule was 1% of the mass of the solution, and the alkaline solution was a saturated solution of calcium hydroxide. Under stirring, the alkali-activated sustained-release capsule was added to the solution, and the solution was sampled at different time periods. The carbon content in the solution was analyzed by TOC to calculate the mass of the released tertiary amine groups. The test results are shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the alkali-activated sustained-release capsules hardly release in aqueous solution, but begin to release slowly in alkaline solution, and accelerate to complete release in 300-500 minutes. This is because the silica shell dissolves slowly in the alkaline solution at the early stage, and when most of the outer silica is dissolved, the dissolution will accelerate.
[0109] Cement mortar fluidity test:
[0110] The alkali-activated sustained-release capsules obtained in each embodiment and comparative example were tested for their effect on the fluidity of cement mortar. The fluidity of cement mortar was tested in accordance with the national standard GB / T 8077-2012 "Test method for homogeneity of concrete admixtures". Naphthalene-based high-efficiency water reducer (Subote -A), the dosage is the mass ratio of the alkali-activated sustained-release capsule to the cement, and the comparison results are shown in Table 1. In the fluidity test, no acrylamide monomer was added to the sample, and the dosage was the mass ratio of the alkali-activated sustained-release capsule to the cement.
[0111] Table 1 Comparison of mortar fluidity test
[0112]
[0113] It can be seen from the data in Table 1 that after adding the above-mentioned silica sustained-release capsules of the present invention, the fluidity of the corresponding cement-based material does not change significantly, which proves that the inorganic admixture has no effect on the working performance of cement.
[0114] In order to verify the performance of the sustained-release material for improving the flexural resistance of cement-based materials of the present invention when applied to cement-based materials, the alkali-activated sustained-release capsules obtained in the above embodiments and comparative examples were mixed with the monomer solution to form solution A, and solution A and solution B were added to the cement-based material at the same time, and the relevant properties of the corresponding cement-based material were measured.
[0115] The mortar material ratio shown in Table 2 is adopted, and the sustained-release material for improving the flexural resistance of cement-based materials prepared by the alkali-activated sustained-release capsule material provided in the above embodiments is added to prepare the mortar. The specific dosage is shown in Table 3, wherein the dosage of the alkali-activated sustained-release capsule is the dosage relative to cement, the dosage of the monomer solution is the dosage of its effective component relative to cement, and the dosage of the B solution is the dosage of its effective component relative to the effective component of the monomer solution. When the mortar is stirred and formed, the A and B solutions are blended to replace the water required in the forming to prepare the mortar, and the mortar is cured at room temperature. At the same time, a comparison group is set up, in which the above-obtained sustained-release capsule is not added to the comparison group, and only acrylamide monomer and ammonium persulfate initiator solution are added.
[0116] Table 2 Mortar mix ratio
[0117]
[0118] Table 3 Proportion of slow-release materials for improving the flexural properties of cement-based materials
[0119]
[0120]
[0121] The mechanical properties of the mortar with different slow-release materials (differentiated according to the dosage of different alkali-activated slow-release capsules) added according to Table 3 for improving the flexural properties of cement-based materials were tested at different ages. The test method is referenced to (Construction and Building Materials, 2013, 49: 121). The test results are as follows:
[0122] Table 4 Mechanical properties of mortar (dosage based on cement mass)
[0123]
[0124]
[0125] As can be seen from Table 4, the flexural and compressive data of the cement test blocks added with the sustained-release capsules provided by the present invention at 7d and 28d are significantly improved compared with the reference and blank, and the difference in the effect of different dosages on the mechanical properties is small. Due to the retarding effect of the monomer, the compressive strength is slightly reduced at 7d. Among them, the 7d compressive and flexural resistance can be improved by 24.7%, and the 28d flexural and compressive resistance can be improved by 48.7%. In addition, since SD-1 does not have a sustained-release coating layer, it directly induces polymerization after being added, resulting in a serious retarding phenomenon, and its compressive and flexural strengths are reduced. At the same time, after 28d of curing, it still has a certain retarding effect.
[0126] These examples prove that the sustained-release capsule material provided by the present invention can be used to enhance the mechanical properties of cement-based materials.
Claims
1. A sustained-release material for improving the flexural resistance of cement-based materials, characterized in that: It comprises a solution A and a solution B; the solution A is prepared by mixing an alkali-activated sustained-release capsule and a monomer solution; The monomer solution is an acrylamide solution or a sodium acrylate solution, and the B solution is an oxidative initiator solution; The alkali-stimulated sustained-release capsule comprises an inner core, an intermediate coating layer and an outer coating layer; the inner core is nano-silicon dioxide, the intermediate coating layer is nano-silicon dioxide modified with tertiary amine groups, and the outer coating layer is nano-silicon dioxide; The mass ratio of the effective ingredient in the monomer solution to the alkali-stimulated sustained-release capsule is 30:1-30; The mass ratio of the effective components in the monomer solution to the effective components in solution B is 30:0.03-0.
3.
2. The sustained-release material for improving the flexural resistance of cement-based materials according to claim 1, characterized in that: The inner core has a diameter of 70-120 nm, the middle coating layer has a thickness of 6-14 nm, and the outer coating layer has a thickness of 8-20 nm.
3. The sustained-release material for improving the flexural resistance of cement-based materials according to claim 1, characterized in that: The nano silicon dioxide modified with tertiary amine groups is prepared by siloxane hydrolysis of diethylaminomethyltriethoxysilane.
4. The slow-release material for improving the flexural resistance of cement-based materials according to claim 1, characterized in that: The oxidative initiator is selected from sodium persulfate and ammonium persulfate.
5. The slow-release material for improving the flexural resistance of cement-based materials according to claim 1, characterized in that: The preparation method of the alkali-stimulated sustained-release capsule specifically comprises the following steps: (1) adding an alkaline solution to an organic solvent to adjust the pH value of the solution system to 11-13; then adding tetraethyl orthosilicate thereto to obtain a precursor solution; Mechanically stirring the precursor solution to obtain a suspension; (2) adding an alcohol solution of tetraethyl orthosilicate to the suspension to cause a siloxane hydrolysis reaction; after the reaction is completed, a core nano-silica is obtained; (3) continuing to raise the temperature of the reaction system to 50-60° C., while adding diethylaminomethyltriethoxysilane to cause a siloxane hydrolysis reaction, and after the reaction is completed, coating the intermediate coating layer onto the surface of the inner core nano-silica; (4) The reaction system is cooled to room temperature, and an alcohol solution of tetraethyl orthosilicate is continuously added to the reaction system to cause a siloxane hydrolysis reaction. After the reaction is completed, the reaction product is post-treated to obtain a solid sample, which is an alkali-activated sustained-release capsule.
6. The slow-release material for improving the flexural resistance of cement-based materials according to claim 5, characterized in that: The alkaline solution in step (1) is one or a combination of sodium hydroxide solution and ammonia water.
7. The slow-release material for improving the flexural resistance of cement-based materials according to claim 5, characterized in that: The organic solvent in step (1) is ethanol or isopropanol.
8. The slow-release material for improving the flexural resistance of cement-based materials according to claim 5, characterized in that: The mass proportions of the raw materials used in the preparation method of the alkali-activated sustained-release capsules are as follows: 2-5 parts of tetraethyl orthosilicate in the step (1), 1-3 parts of tetraethyl orthosilicate in the step (2), 1-3 parts of diethylaminomethyltriethoxysilane in the step (3), and 2-5 parts of tetraethyl orthosilicate in the step (4).
9. The use of the slow-release material for improving the flexural properties of cement-based materials according to any one of claims 1 to 8, characterized in that: The solution A and solution B in the slow-release material for improving the flexural resistance of cement-based materials are added to cement-based materials respectively, wherein the mass of the effective component of the monomer solution is 1%-3% of the total mass of the gelling material in the cement-based material.
Citation Information
Patent Citations
Additive for improving flexural strength and tensile strength of cement-based material and preparation method of additive
CN104446102A
Additive capable of improving bending strength and tensile strength of cement base material and its preparation method
CN104609759A
Slow-release coagulation-accelerating composite material, preparation method thereof and application of slow-release coagulation-accelerating composite material in cement-based material
CN114685077A
Organic-inorganic nano composite microcapsule material as well as preparation method and application thereof
CN116514441A